Electrical and physical property study of thin films grown by laser molecular beam epitaxy - Choy, Chang Ye. (2009)
In this project, 50nm/100nm-thick epitaxial SrRuO3 and BaTiO3 thin films were grown on <100>, <110> and <111> SrTiO3 substrates by Laser Molecular Beam Epitaxy (LMBE) at 650°C. Lift-off process is performed to create the metallic contact for the resistivity characterization on SrRuO3/ SrTiO3 and capacitance characterization on BaTiO3/ SrTiO3.